Credibility in public institutions in Colombia: a challenge to overcome (2015)
In this document was observed the big problem that represents the corruption to Colombia and how it triggers various events that affect the entire. These cases of corruption increasingly deteriorate the credibility of citizens in state institutions. Therefore, the objective of this study was to make a reflection, mainly theoretical, about the importance of transparency as a tool for citizen participation in monitoring and effective management of their rulers and resulting increase credibility of citizens in state institutions. The definition of transparency, access to information, accountability and regulatory evolution as means of enhancing the credibility of the State was consulted. Additionally, the classification of Colombia in transparency indicators were reviewed and compared to other countries in Latin. The progress achieved in Chile which allowed them to develop a credible exercise demonstrated high levels of transparency was highlighted. We conclude that in Colombia you have the rules as Law 1712 of March 6, 2014, but it takes a greater commitment of governments to implement the rules effectively and generate participation spaces where isn't made for information, but are spaces that give opportunity to review, reflection and development of public policies to benefit the entire population.